PENGARUH MULTIDIMENSI KOMITMEN PROFESIONAL TERHADAP PERILAKU AUDIT DISFUNGSIONAL - Silaban, Adanan (JURNAL AKUNTANSI DAN AUDITING, 2011)
The purposes of this study are two fold. First is to examine validity of Meyer et al.’s (1993)three-component model of commitment professional among on auditor which working in auditfirms. The second is to examine relations dimension of commitment professional todysfunctional audit behaviors. Dysfunctional audit behaviors include auditors’ act duringperformance audit program which directly or indirectly reduced audit quality namely auditquality reduction (AQR) and Under Reporting of Time (URT) behaviors. This study conductedwith survey method on auditors working in audit firms at three mayor cities in Indonesia i.e.;Jakarta, Surabaya, and Medan. Research samples are 348 respondents. Data analysis withStructural Equation Modeling used AMOS. The result of confirmatory factor analyses andtest of reliability and validity provide support for three separate dimensions of professionalcommitment. Affective professional commitment has negative associated with AQR behavior,but it relationship with URT behavior is not significant. The influence of continuanceprofessional commitment to AQR and URT behaviors is not significant. Normativeprofessional commitment is inversely related to AQR and URT behaviors. The results ofresearch contribute to literature and interpreting the prior research and for consideringfuture research on auditors’ commitment professional are presented.Keywords:dysfunctional audit behaviors, audit quality reduction behavior, underreporting oftime behaviors, multi-dimension professional commitment.